The ways of developing a culture of education quality and academic integrity in the contemporary university - I. I. Maslikova (Ukrainian Cultural Studies, 2021)
The article deals with the analysis of the legislative provisions and regulations in the field of higher education in Ukraine and the regulatory framework of Taras Shevchenko National University of Kyiv. These legislative acts and regulations lay the foundation for the development of a culture of education quality and the corporate culture of the university. The study of the state of ensuring academic integrity within the framework of the AcademIQ project "Initiative for Academic Integrity and Quality Initiative", especially research of the interpretation of the survey of the teachers and students of Taras Shevchenko National University of Kyiv, allowed to outline the ways of developing a culture of quality in higher education, corporate culture of the university and academic integrity. The development of corporate culture and the quality of education at the university is associated with the articulation of the key values of the contemporary university community and the ethical virtues of all participants in the educational process. These values and virtues should be determined in broad discussions among students, teachers, and administration. The implementation of these values is possible through joint scientific, educational, methodological, cultural and social events, which can bring together all members of the university community. Teachers and students can internalize these values in different training courses. Ensuring academic integrity is possible through its procedural and institutional design. The important way for developing of academic integrity is raising awareness of all participants in the educational process through the increase of the content of internet sites, through broad discussions about complex cases of academic integrity, through the introduction of training modules into academic courses "Professional and Corporate Ethics", "Ethics", "Introduction on University Studies", "Academic Writing" .